Exosomes Derived From M2 Microglia Cells Attenuates Neuronal Impairment and Mitochondrial Dysfunction in Alzheimer’s Disease Through the PINK1/Parkin Pathway - Li, Nan; Shu, Jun; Yang, Xiaoyan; Wei, Wenshi; Yan, Aijuan (Frontiers in Cellular Neuroscience, 2022)
The accumulation of abnormal aggregation of amyloid-β plaques is one of the most distinguishing pathologies of Alzheimer’s disease (AD) and is highly toxic to neurons. Exosomes have demonstrated great potential for AD therapy. However, the impact and underlying mechanism of M2 microglia-derived exosomes (M2-EXOs) in AD progression and outcome are seldom explored. Therefore, we employed an Aβ1-42 oligomer(Aβ)-induced AD model in neuronal HT-22 cells and 7-month-old APP/PS1 mice to investigate the effects of M2-EXOs on AD. We revealed that the AD cell model established by Aβ was accompanied by the upregulation of Aβ1-42, neuronal death, alternation of mitochondrial function and autophagy. M2-EXOs can be internalized by HT-22 cells and MAP2-positive neuronal cells in APP/PS1 mice, and exert neuroprotective functions. Specifically, the administration of M2-EXOs in the AD cell model partially increased cell viability, restored the destruction of mitochondrial membrane potential， and reduced the accumulation of reactive oxygen species inside the mitochondria and cells in a dose-dependent manner. Moreover, we demonstrated that PINK1/Parkin mediated mitophagy was enhanced, while incubation with M2-EXOs decreased beclin1, LC3II, PINK1, and Parkin expression levels. Finally, we observed that compared with APP/PS1 mice treated with PBS, the application of M2-EXOs could decrease Aβ plaque deposition and minus Aβ oligomer expression along with improved PINK1/Parkin pathway-mediated autophagy. Overall, our results imply that M2-EXOs play a protective role in the pathogenesis of AD by ameliorating PINK1/Parkin-mediated mitophagy, indicating that it may provide a novel therapeutic strategy to treat AD.